Electrically-evoked responses for retinal prostheses are differentially altered depending on ganglion cell types in outer retinal neurodegeneration caused by Crb1 gene mutation - Roh, Hyeonhee; Otgondemberel, Yanjinsuren; Eom, Jeonghyeon; Kim, Daniel; Im, Maesoon (Frontiers in Cellular Neuroscience, 2023)
Background: Microelectronic prostheses for artificial vision stimulate neurons surviving outer retinal neurodegeneration such as retinitis pigmentosa (RP). Yet, the quality of prosthetic vision substantially varies across subjects, maybe due to different levels of retinal degeneration and/or distinct genotypes. Although the RP genotypes are remarkably diverse, prosthetic studies have primarily used retinal degeneration (rd) 1 and 10 mice, which both have Pde6b gene mutation. Here, we report the electric responses arising in retinal ganglion cells (RGCs) of the rd8 mouse model which has Crb1 mutation. Methods: We first investigated age-dependent histological changes of wild-type (wt), rd8, and rd10 mice retinas by H&E staining. Then, we used cell-attached patch clamping to record spiking responses of ON, OFF and direction selective (DS) types of RGCs to a 4-ms-long electric pulse. The electric responses of rd8 RGCs were analyzed in comparison with those of wt RGCs in terms of individual RGC spiking patterns, populational characteristics, and spiking consistency across trials. Results: In the histological examination, the rd8 mice showed partial retinal foldings, but the outer nuclear layer thicknesses remained comparable to those of the wt mice, indicating the early-stage of RP. Although spiking patterns of each RGC type seemed similar to those of the wt retinas, correlation levels between electric vs. light response features were different across the two mouse models. For example, in comparisons between light vs. electric response magnitudes, ON/OFF RGCs of the rd8 mice showed the same/opposite correlation polarity with those of wt mice, respectively. Also, the electric response spike counts of DS RGCs in the rd8 retinas showed a positive correlation with their direction selectivity indices (r=0.40), while those of the wt retinas were negatively correlated (r=-0.90). Lastly, the spiking timing consistencies of late responses were largely decreased in both ON and OFF RGCs in the rd8 than the wt retinas. Conclusions: Our results indicate the electric response features are altered depending on RGC types even from the early-stage RP caused by Crb1 mutation. Given the various degeneration patterns depending on mutation genes, our study suggests the importance of both genotype- and RGC type-dependent analyses for retinal prosthetic research.